Biomechanical signals for external biofeedback to improve swimming techniques - Chollet, D.; Micallef, J. P.; Rabischong, P. (Swimming Science V, 1979)
The present research was the result of a number of practical questions with direct applications: How can one analyze and then provide a swimmer with information on his or her motor patterns during swimming? Swimmers have an objective means for evaluation at their disposal, but this is available only after the performance is completed. They may also estimate their efficiency in real time, but their biological perceptions are not very precise or objective. The aim of this research was to develop an experimental device that would permit the measurement of the force or pressure on the hand during the propulsive action in crawl swimming and to transform this information into an audible signal that could be transmitted to the swimmer while swimming.